(3/5)(y+1)=(4/5)y

Simple and best practice solution for (3/5)(y+1)=(4/5)y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3/5)(y+1)=(4/5)y equation:


(3/5)(y+1)=(4/5)y

We simplify the equation to the form, which is simple to understand
(3/5)*(y+1)=(4/5)y

Simplifying:
( + 0.6)*(y+1)=(4/5)*y

Simplifying:
( + 0.6)*(y+1)=( + 0.8)*y

Reorder the terms in parentheses
multiplication of parentheses
( + 0.6y + 0.6)=( + 0.8)*y



Remove unnecessary parentheses
+ 0.6y + 0.6=( + 0.8)*y

Reorder the terms in parentheses
+ 0.6y + 0.6=( + 0.8y)

Remove unnecessary parentheses
+ 0.6y + 0.6=0.8y

We move all terms containing y to the left and all other terms to the right.
+ 0.6y-0.8y=-0.6

We simplify left and right side of the equation.
-0.2y=-0.6

We divide both sides of the equation by -0.2 to get y.
y=3

See similar equations:

| 2x-7x+2=x-8+10 | | -3/5m=-12 | | 16(y+2)=12y+16 | | 4(a+9)=64 | | (y/2)+5=11 | | 2/y=5/9 | | 23=5-2/3m | | (y/2)+5+11 | | -3/10y=-12 | | 43=6c-5 | | Y/4=5/8 | | 9=2x-2 | | 28=2y+8-5y | | 5x+a=128 | | -10/-21 | | x+20=2x-60 | | 5(4x-5)=23-4(3x-4) | | 22r=-176 | | 9e-2=43 | | -28=2y+8+5y | | v-10=-18 | | m-16=43 | | 5(1)-7y=12 | | (13a-13)(-18asq+13)-7= | | 3+3n-2=9n+8-5n | | -5x+4/3=8/3 | | (x+3)-2(2-4x)=3(x+5)-4 | | a+y=23 | | 3x-2=(5x-6/4) | | X+20+y-20=180 | | 3z-i*z+1=10 | | 3m+6=9m |

Equations solver categories